Tracing Malay traditional villages in the mukim Setapak from socio-cultural and historical lenses - Mansor Majdin, Mohamad Firdaus; Mohd, Siti Hadija; Sulkafle, Mohamad Hazizie (ASIAN SCHOLARS NETWORK, 2025)
At present, there exist unique hybrid cultural practices and traditions among the locals that are interestingly evident in their daily socio-economic activities, especially among those who reside in several traditional villages in the mukim of Setapak (district of Gombak). A quick glance at them reveals that these practices, strictly speaking, are quite unique to pure local Malay practices and traditions. A preliminary study further revealed that many of these villagers are originally from Indonesia and belong to different ethnicities and clans. They migrated from the Indonesian islands and found their way to Selangor, eventually coexisting with the local Malays. This preliminary paper employs a historical research method to investigate how the locality gradually becomes a melting pot of diverse socio-cultural traditions practised by its people. Ultimately, this study demonstrates that the diversity results from the arrival of Malays from different clans of the Indonesian islands, who were driven by socio-political and economic factors and eventually assimilated with local practices in the area.